Spatially explicit estimation of occupancy, detection probability and survey effort needed to inform conservation planning - Olea, Pedro; Mateo Tomás, Patricia; Frutos, Ángel de (Diversity and Distributions, 2011)
Aim It is increasingly recognized the importance of accounting for imperfect detection in species distribution modelling and conservation planning. However,the integration of detectability into a spatially explicit frame has received little attention. We aim (1) to show how to develop distribution maps of both detection probability and survey effort required to reliably determine a species presence/absence and (2) to increase awareness of the spatial variation of detection error inherent in studies of species occurrence. Location North-western Spain. Methods We registered the presence/absence of the endangered Egyptian vulture (Neophron percnopterus) in 213 surveys performed in 40 of 104 territories once known to be occupied. We model simultaneously both detection probability and occurrence,using site occupancy modelling. With the resulting regression equations,we developed distribution maps of both detection probability and required sampling effort throughout the area. Results Of the studied territories,72.5% were detected as occupied,but after accounting for imperfect detection,the proportion of sites truly occupied was 79%. Detectability decreased in territories with higher topographical irregularity and increased with both the time of day of the survey and the progress of the season. Spatial distribution of detectability showed a mainly north-south gradient following the distribution of slope in the area. The likelihood of occupancy increased with rockier,less forested surface and less topographical irregularity within the territory. A minimum of five surveys,on average,are needed to assess,with 95% probability,the occupancy status of a site,ranging from ?3 to >24 visits/territory depending on survey- and site-specific features. Main conclusions Accounting for detectability and its sources of variation allows us to elaborate distribution maps of detectability-based survey effort. These maps are useful tools to reliably assess (e.g. with 95% probability) occupancy status throughout a landscape and provide guidance for species conservation planning. © 2011 Blackwell Publishing Ltd.
Keywords: biological survey; conservation planning; detection method; ecological modeling; endangered species; estimation method; landscape ecology; population distribution; raptor; regression analysis; sampling; spatial analysis; spatial variation; species conservation; topography; Spain; Neophron percnopterus; Detection probability; Monitoring programmes; Neophron percnopterus; Presence-absence; Site occupancy modelling; Species distribution models; 24 Ciencias de la Vida; ODS 13 - Acción por el clima; ODS 15 - Vida de ecosistemas terrestres; ODS 14 - Vida submarina